Phenylacetaldehyde induced olfactory conditioning in Drosophila melanogaster (Diptera: Drosophilidae) larvae. - Ali, M.Z.; Anushree, A.; Bilgrami, A.L.; Ahsan, A.; Ola, M.S.; Haque, R.; Ahsan, J. (Journal of insect science (Online), 2023)
Phenylacetaldehyde (PAH), an aromatic odorant, exists in varied fruits including overripe bananas and prickly pear cactus, the 2 major host fruits of Drosophila melanogaster. It acts as a potent ligand for the Ionotropic receptor 84a (IR84a) and the Odorant receptor 67a (OR67a), serving as an important food and courtship cue for adult fruit flies. Drosophila melanogaster larvae respond robustly to diverse feeding odorants, such as ethyl acetate (EA), an aliphatic ester. Since the chemical identity and concentration of an odorant are vital neural information handled by the olfactory system, we studied how larvae respond to PAH, an aromatic food odorant with aphrodisiac properties for adult flies. Our findings revealed that PAH attracted larvae significantly in a dose-dependent manner. Larvae could also be trained with PAH associated to appetitive and aversive reinforcers. Thus, like EA, PAH might serve as an important odorant cue for larvae, aiding in food tracking and survival in the wild. Since IR84a/IR8a complex primarily governs PAH response in adult flies, we examined expression of Ir84a and Ir8a in early third-instar larvae. Our experiments showed the presence of Ir8a, a novel finding. However, contrary to adult flies, PAH-responsive Ir84a was not found. Our behavioral experiments with Ir8a1 mutant larvae exhibited normal chemotaxis to PAH, whereas Orco1 mutant showed markedly reduced chemotaxis, indicating an OR-mediated neural circuitry for sensing of PAH in larvae. The results obtained through this study are significantly important as information on how larvae perceive and process PAH odorant at the neuronal level is lacking.